Evaluation of polyphenol rich papaya (Carica papaya L.) leaf and its extracts on rumen microbes, biohydrogenation and methane production - Jafari, Saeid (2016)
Methane (CH4) emission from enteric fermentation is one of the causes of climate changes and global warming. Rumen biohydrogenation (BH) is also detrimental to human health because of increasing the risk of cardiovascular diseases. The effect of increasing inclusion levels of papaya leaf (PL), PL extract (PLE) and PL with different solvent fractions (PLFs) on biohydrogenation (BH) of polyunsaturated fatty acids (PUFA), microbial quantification and fermentation characteristics were studied. For three in vitro studies, PL at different concentrations: 0 (control; CON, 50% alfalfa hay (AH) + 50% concentrate), 15% of AH in substrate replaced by PL (18.75 mg /250 mg dry matter, DM), 25% of AH in substrate replaced by PL (31.25 mg/250 mg DM) and 50% of AH in substrate replaced by PL (62.50 mg/250 mg DM) were mixed with 30 ml of buffered rumen fluid and were incubated for 24 h. CH4 production (mL/250mg DM) declined at a decreasing rate (linear, p = 0.03) with increasing levels of PL. Supplementation of the diet with PL significantly (P<0.05) decreased the rate of BH of LA and C18-PUFA after 24 h of incubation, especially at the higher inclusion rate, resulting in an increased production of rumen BH intermediates such as conjugated linoleic acid (CLA), whereas saturated fatty acid (SFA) decreased in the rumen fluid after 24 h of incubation. Total methanogens (P<0.05) were lower in MPL (-12%) and HPL (-16%) compared to CON. Moreover, there were increases in total bacterial population (HPL: +5%) and Butyrivibro fibrisolvens (MPL: +20; HPL: +23%) among PL treatment groups compared to the CON group. PLE at different concentrations with no addition of PLE (CON, 0), 5 mg /250mg DM (low leaf extract: LLE), 10 mg /250mg DM (medium leaf extract: MLE) and 15 mg /250mg DM (high leaf extract: HLE) was mixed with 30 ml of buffered rumen fluid and were incubated for 24 h. CH4 production decreased (P<0.05) with increasing levels of PLE. Supplementation of the diet with PLE significantly (P<0.05) decreased the rate of BH of oleic acid (OA), linoleic acid (LA), α-linolenic acid (LNA) and C18-PUFA compared to CON after 24 h incubation resulting in increased concentrations of BH intermediates such as vaccenic acid (VA), rumenic acid (RA) and t10c12 CLA. Total protozoa and methanogen population in HLE decreased (P<0.05) compared to CON, but the total bacteria and Butyrivibrio fibrisolvens population were higher (P<0.05) in CON compared to the PLE treatment groups. Different solvent fractions of PL (PLFs; Hexane fraction, Chloroform fraction, Ethyl acetate fraction, Butanol fraction and water fraction) at a concentration of CON with no PLFs (0) and 15mg /250 mg DM which were equivalent to 0 and 60 g/kg DM, respectively were mixed with 30 mL of buffered rumen fluid and were incubated for 24 h. CH4 production was highest (P<0.05) for CON (7.65) and lowest for chloroform fraction (5.41) compared to other PLFs at 24 h of incubation. Supplementation of the diet with PLFs significantly (P<0.05) decreased the rate of BH of OA, LA and LNA compared to CON after 24 h of incubation. The chloroform fraction had the lowest BH of OA (45.01%) and LA (54.65%) among treatments. Total protozoa and total methanogen populations in PLFs decreased (P<0.05) compared to CON, but the population of Butyrivibrio fibrisolvens was higher (P<0.05) in CON compared to PLFs treatment groups. These in vitro results indicate that PL, PLE and PLFs supplementation as the substrate decreased BH of PUFA, inhibited rumen methanogenesis without adversely affecting other rumen fermentation characteristics in rumen fermentation liquid. For in vivo study, four fistulated adult Kajang cross-bred goats (39.0 ± 0.75 kg mean ± standard error) were used in a cross-over design study to test the effect of PL on rumen fermentation characteristics, rumen microbial population and FA composition of rumen fluid obtained at different times of sampling (0, 2, 4, 6 and 8 h). Goats were fed twice daily to the following diets: (CON, 50 % concentrate + 50% AH), 25% AH in basal diet replaced by PL (MPL), and 50% AH in basal diet replaced by PL (HPL). Rumen samples were collected at the end of the experiment (3rd weeks). Supplementation of the diet with PL significantly (P<0.05) decreased the rate of rumen BH of LA after different hours of feeding at the higher inclusion of PL (HPL), resulting in an increased concentration of rumen intermediate products such as CLA e.g. t10 c12, whereas SFA and stearic acid (SA) decreased (P<0.05) in the rumen fluid and blood plasma, respectively. The concentration of LNA was higher (P<0.05) in the blood of goats fed PL especially HPL, compared to the goats receiving only the basal diet with no PL inclusion (CON). The Butyrivibrio fibrisolvens population as determined by real-time PCR at the end of the feeding trial was higher (P<0.05) for MPL (+8%) and HPL (+16 %) in the rumen of goats compared to the CON. Methanogenic bacteria (log10cell/L) decreased (P<0.05) in PL treatment groups. In summary, this research revealed that supplementation of diets with different levels of PL even as a whole or as the extract (PLE and PLFs) plays an important role in affecting rumen microbial fermentation characteristics resulting in a reduction of CH4 production (in vitro) and BH of FA (in vitro and in vivo).